M. Mažvydo raštų kalba - Zinkevičius, Zigmas (Baltistica, 1979)
THE LANGUAGE OF MAŽVYDAS' WRITINGSThe native dialect of Martynas Mažvydas – the author of the first Lithuanian printed boo – has not yet been established. Some investigators (A. Schleicher, V. Grinaveckis) have considered him to be born in the region of Klaipėda or generally in the Dukedom of Prussia (P. Pakarklis), other scholars (K. Būga, Chr. S. Stang, J. Senkus) considered him to have come from the north-western part of the Samogitian dialect area, still others (A. Salys) – from the south-eastern part of that dialect area. However, in their investigations they all confined themselves solely to the linguistic analysis of the first Lithuanian book – Mažvydas' Catechism of 1547, while his other writings were almost totally ignored.The author of the present paper conducted a linguistic research of all Mažvydas' writings, including a better copy of the Catechism of 1547, obtained from the M. Gorky Library of Odessa and at the present time preserved at the Vilnius University Library. Dialect features of the writings were compared in great detail to the corresponding peculiarities of the present-day Lithuanian dialects and in the first place to those of the Samogitian dialects.The conclusions of the study were presented in the article published in parts in Baltistica, vols. XIII, 2, XIV, 1–2 and XV, 1. The following are the main conclusions of the study.Mažvydas' native dialect is to be localized in the south-western part of Southern Samogitian area; cf. the map in Baltistica XIII, 2, p. 369.The High Lithuanian dialectal characteristics appeared in the first Lithuanian book not due to Mažvydas' conscious efforts to conform to High Lithuanian (as previously many scholars were apt to assume) but owing to his being born in a dialectally mixed family: his father must have been a Samogitian, whereas his mother was a western High Lithuanian, a speaker of its northern subdialect. The analysis of Mažvydas' early writings (Baltistica XIV, 2) indicates that their dialectal features coincide with those of the writings of Vilentas who was his cousin. Later living in the Dukedom of Prussia, Mažvydas tried to adjust himself to the local West High Lithuanian dialect — more precisely to the dialect of Ragainė which did not differ much from Vilentas' native dialect.The interpretation of the sounds and forms of Mažvydas' works is closely connected with the establishment of his native dialect. The sequels of the article in Baltistica, XIV, 2 and XV, 1 deal with the analysis of the major phonetic, grammatical and lexical characteristics of Mažvydas' native dialect arid the elucidation of their developments in the period of over 400 years.
Keywords: M. Mažvydo raštai; senieji raštai; morfologija